PENINGKATAN KUALITAS PEREMPUAN MENJADI GENERASI KUAT DAN HEBAT - Eva Muti’ah; Wulan Riska Dewi; Handy Setiayadi; Agustina Agustina; Uli Wildan Nuryanto; Basrowi Basrowi (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Women in rural areas do not fully realize that in a woman there is great potential to produce a work. Many women have skills that are not developed or even forgotten. For this reason, there needs to be support so that women in rural areas are able to develop themselves and play an active role in family resilience, so as to create creative, innovative, and intelligent women. This PKM aims to analyze the benefits of skills training on improving the quality of women. The methods used in this PKM are counseling and practice methods. Data collection techniques through pre-test and post-test. The results of PKM show that there is a significant change in the benefits of skills training to improve women's quality